Kreatifitas Petani Melalui Gerbas Tani dalam Peningkatan Ekonomi - Sri Sumarliani; Sri Hastuti (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2023)
The Agricultural Sector plays a very important role in national development. Agriculture is needed, as long as humans live and as long as agriculture becomes a necessity. The most important sector in increasing added value for rural and urban communities. The presence of the nation's future youth will be better if they are involved in facing challenges in developing productivity in agriculture. The majority of people in the village make a living as farmers. In order to meet economic needs, innovation and creativity are needed so that the selling value of agricultural products increases. By going through gerbas tani (Vegetable Shopping Movement at Farmers) people buy directly to these farmers which is clearly the price offered is higher than the price of traders. The innovation and creativity of the Vegetable Shopping Movement from Farmland (Gerbas Tani) is expected to be a creative idea for villages and farmer groups in increasing economic income from agricultural products. This community service activity is the creativity of farmers in improving the farmer's economy and the added value of agricultural products. Through Gerbas Tani, the youth also participated by opening cooperation with schools to harvest fruit as a form of educational tourism in agriculture.